Femoral neck fragility: genes or environment? - Loveridge, N; Reeve, J (2004)
As with other diseases that show exponentially increasing rates, hip fracture probably requires multiple prior events to become manifest. It is common ground that there are genetic, environmental, lifestyle and perhaps dietary determinants of risk of osteoporotic fracture as well as interactions between them. The key to secondary prevention is the understanding of how these components can be integrated into an effective assessment of the major risks of hip fracture after a previous fracture has occurred. The key to primary prevention is to understand both the pathological and physiological basis of hip fragility. It is not unreasonable to suppose that in a western lifestyle our limited and stereotypic patterns of locomotion from middle age onwards may offer considerably less protection than, for example, the more physically demanding activity of subsistence farming.